THE IMPACTS OF STUTTERING SHIFTS TO THE TRANSLATION QUALITY OF THE ADVENTURE OF TINTIN COMICS - Rudy Prasojo (UIN Raden Mas Said Surakarta, 2019)
This article aims to discuss how stuttering utterances are translated from English to Bahasa Indonesia. Data in the form of stuttering utterances spoken by Captain Haddock, a character in The Adventure of Tintin comic series, were collected to see how the translator decided to convert those utterances into Bahasa Indonesia. The method employed in this research is the qualitative-descriptive in which the data were taken from two sources(English and Bahasa Indonesia). The finding shows that there are three categories of stuttering initiator namely:Â intoxicated, emotions, and situations. Each category is classified based on its types, namely repetitions, hesitations, and fillers. In addition, the finding also shows that each type of stuttering was placed in a different concept on its target language named shifting. It can further be classified into preserved, altered, and omitted. Each of them affects the meaning and the message of stuttering utterances in the translation version. Finally, the statistic indicates that every type of shifting gives a significant impact to the translation quality.